Implementing intravenous iron for maternal anemia in Nigeria: A qualitative study of healthcare provider experiences using the normalization process theory - Damilola Onietan; Chisom Obi‑Jeff; Yusuf Adelabu; Mobolanle Balogun; Opeyemi Akinajo; Esther O. Oluwole; Aduragbemi Banke‑Thomas; Bosede B. Afolabi; Ejemai Eboreime (PLoS ONE, 2026)
Background Maternal anemia remains a significant public health challenge in Nigeria, affecting approximately 25–46% of pregnant women and contributing to adverse maternal and neonatal outcomes. Intravenous (IV) iron provides a promising alternative to conventional oral iron supplementation for managing moderate to severe maternal anemia; however, its implementation in resource-limited settings faces numerous challenges. This study aimed to understand how the implementation of IV iron became embedded in everyday practice, including factors influencing skilled healthcare providers’ (SHPs) engagement, workflow integration processes, and sustainability. Methods This was a qualitative study embedded within the Implementation Research for Intravenous Iron Use in Pregnant and Postpartum Women in Nigeria (IVON-IS) project across six healthcare facilities in Lagos, Nigeria. Eighteen key informant interviews were conducted with purposively sampled SHPs across the six IVON-IS facilities. The data were analyzed deductively based on the Normalization Process Theory (NPT) constructs (coherence, cognitive participation, collective action, and reflexive monitoring), and inductively to identify themes related to each of these constructs. Results Our study revealed strong coherence among SHPs regarding the purpose and benefits of IV iron compared to traditional treatments. Cognitive participation varied across facilities, with leadership support and patient-centred motivation emerging as critical facilitators. Collective action was faced with challenges, including workflow disruptions, staffing constraints, and space limitations, despite adequate resource provision. Reflexive monitoring processes were robust, with providers continuously evaluating effectiveness through clinical outcomes and patient feedback while expressing concerns about long-term sustainability. Conclusion The implementation of IV iron for maternal anemia in Nigeria demonstrated variability across NPT constructs, with strong coherence and reflexive monitoring but challenges in cognitive participation and collective action. Critical success factors included strong leadership support, adequate resource provision, continuous quality improvement processes, and proactive sustainability planning. The findings from this study provide valuable guidance for scaling up IV iron use as part of comprehensive maternal health services in Nigeria and similar resource-constrained settings.